Computational study of absorption spectra of the hhotoconvertible fluorescent protein EosFP in different protonation states - Imhof, Petra (Journal of chemical theory and computation, 2012)
Absorption spectra of the green-to-red convertible fluorescent protein EosFP have been computed in a hybrid quantum mechanical/molecular mechanical (QM/MM) framework. The experimentally observed absorption maximum at ∼390 nm is well reproduced by the protein with a neutral chromophore, and the anionic form is computed to absorb close to the experimentally determined maximum at ∼500 nm. Absorption of a zwitterionic form is calculated to lie in the same spectral region; however, this species cannot be unambiguously assigned to the experimental spectra. Variation of the protonation states of residues surrounding the chromophore do not have significant impact on the positions of the absorption maxima. In particular, protonation of Glu212 leaves the calculated spectra largely unaffected. This is consistent with the spectra of the E212Q mutant, which differ from the wild-type spectra only in the intensities but not in the positions of the absorption bands.
Gesehen am 20.11.2018